Trends in oral anticoagulant prescribing in individuals with type 2 diabetes mellitus: A population-based study in the UK - Hassan Alwafi (2020)
© 2020 Author(s). Objective To evaluate oral anticoagulant (OAC) prescribing trends in type 2 diabetes mellitus (T2DM) in the UK from 2001 to 2015. Design A cross-sectional drug utilisation study. Setting Electronic health records from The Health Improvement Network primary care database in the UK. Participants Individuals with T2DM who received a record of OAC prescription. Outcome measures The prescribing trends of OAC medications in individuals with T2DM were examined from 2001 to 2015, stratified by age, gender and therapeutic classifications. Results A total of 361 635 individuals with T2DM were identified, of whom 36 570 were prescribed OAC from 2001 to 2015. The prevalence of OAC prescribing increased by 50.0%, from 1781 individuals receiving OAC prescriptions (IROACP) (4.4 (95% CI 4.2 to 4.6) per 100 persons) in 2001, to 17 070 IROACP (6.6 (95% CI 6.5 to 6.7) per 100 persons) in 2015. The prevalence of warfarin prescribing decreased by 14.0%, from 1761 individuals receiving warfarin prescriptions (IRWP) (98.9 (95% CI 98.4 to 99.4) per 100 persons) in 2001, to 14 533 IRWP (85.1 (95% CI 84.6 to 85.7) per 100 persons) in 2015. This corresponded with increased prescribing of direct oral anticoagulants (DOACs), from 18 individuals receiving DOAC prescriptions (IRDOACP) (0.1 (95% CI 0.08 to 0.23) per 100 persons) in 2010, to 3016 IRDOACP (17.6 (95% CI 17.1 to 18.2) per 100 persons) in 2015, during the same period. Conclusions Prescribing of OACs in individuals with T2DM increased from 2001 to 2015. Since the introduction of DOACs, there has been a clear shift in prescribing towards these agents. Future studies are needed to assess the safety of coadministration of OAC medications and antidiabetic therapy with T2DM.